The Analysis of Tax Planning Application of Article 21 Income Tax for Permanent Employees in Efficiency of Tax Expenses at CV Prima Abadi - Bambang W; N K Sukasih; L M Wahyuni (Jurusan Akuntansi Politeknik Negeri Bali, 2019)
This research aims to determine the comparison and the influence of the implementation of tax planning of article 21 income tax on the efficiency of tax expense on CV Prima Abadi. The focus of this research is tax planning through three methods of withholding Article 21 income tax, and there are three methods are gross method, net method and gross up method. The data analysis technique used in this research are quantitative descriptive analysis technique. Based on the results of research, it can be concluded that applying the gross up method is more efficient to provide savings than doing the net method and gross method, because the cost of article 21 income tax of the employees may be charged on a fiscal basis. The income tax economizing of company owed in 2018 amounted to Rp.10.025.371,00. However, as result of replacing the enjoyment into allowances, the company paid an additional article 21 income tax amounted to Rp.6.686.247,00. So the total savings of company Income Tax after the increasing of the article 21 income tax is Rp.3.339.124,00. CV Prima Abadi should change the method of calculating the deduction of Income Tax Article 21 from the net method into a gross up method.